Shell Polymorphism in the Intertidal Gastropod Pachymelania fusca (Sorbeoconcha: Hemisinidae) - E., Asuquo, Philomena; E., Essien, Eyo; T., Ifon, Honor; Echaami, Eneji, Divine (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Studies to understand the progress of microevolution in aquatic terrains are limited to a few species due to the considerable technical obscurity involved in analyzing the genetic status of diverse traits. The present study adopted a traditional morphometric technique to examine shell polymorphism within the population of the intertidal gastropod (Pachymelania fusca, Gmelin) on the mudflats of the Calabar River, Nigeria. A total of 198 specimens were sampled randomly along the intertidal mudflats (Nsidung, Esukutan, Adiabo) from July to September 2021. The specimens were identified in the field based on standard taxonomic keys and further classified into three morphs based on shell wrinkling: unwrinkled, intermediate, and wrinkled. Each specimen was morphometrically assessed with 9 allometrically treated traits and 2 multivariate markers. Results revealed that the first principal component was responsible for 95.6% of the variance. The leave-one-out classification model correctly assigned 64.0% of individual periwinkles into two morphologically separate groups (unwrinkled and wrinkled), with 17.6% and 47.1% of the intermediate group misclassified as unwrinkled and wrinkled, respectively. The group classification in the present study suggests that selection for shell wrinkling could not be the only determinant of shell polymorphism in P. fusca. Further molecular studies could reveal underlying drivers of shell polymorphism in the intertidal gastropod. Also, cross-breeding experiments could determine if the intermediate form was a copulation or hybridization result between the unwrinkled and the wrinkled forms.